Structural evidence for extracellular silica formation by diatoms - Mayzel, Boaz; Aram, Lior; Varsano, Neta; Wolf, Sharon G.; Gal, Assaf (Nature communications, 2021)
The silica cell wall of diatoms, a widespread group of unicellular microalgae, is an exquisite example for the ability of organisms to finely sculpt minerals under strict biological control. The prevailing paradigm for diatom silicification is that this is invariably an intracellular process, occurring inside specialized silica deposition vesicles that are responsible for silica precipitation and morphogenesis. Here, we study the formation of long silicified extensions that characterize many diatom species. We use cryo-electron tomography to image silica formation in situ, in 3D, and at a nanometer-scale resolution. Remarkably, our data suggest that, contradictory to the ruling paradigm, these intricate structures form outside the cytoplasm. In addition, the formation of these silica extensions is halted at low silicon concentrations that still support the formation of other cell wall elements, further alluding to a different silicification mechanism. The identification of this unconventional strategy expands the suite of mechanisms that diatoms use for silicification. Silica formation in diatoms is of interest for a range of different subjects from biomimetics to oceanography. Here the authors study the formation of silicified extensions in diatoms and find that unlike cell wall elements, that form in the cytoplasm, the extensions have a different formation mechanism outside the cytoplasm.